Sosialisasi Akuntabilitas Laporan Keuangan Untuk Mengantisipasi Tax Dispute Pada Perusahaan Travel Dan Biro Perjalanan Wisata - Setyowati, Tri Mulyani; Lesmini, Lis; Wardhana, Aditya (Jurnal Abdimas Transportasi & Logistik, 2023)
Every company running its business requires the recording of its transactions into financial statements in accordance with accounting standards. PT. Safari Jiyadul Haramain, as a partner in this community service, is one of the travel companies for travel agencies for Muslim pilgrims. As a taxable entrepreneur, running its business requires recording all operational transactions into accountable financial statements. The problem for partners is that there is still a lack of knowledge of human resources related to making financial statements and tax reporting, as well as information about taxation, so it is feared that it can potentially cause tax disputes. The purpose of this activities is to provide socialization regarding financial statement accountability to anticipate tax disputes in travel companies and travel agencies. The method of implementing online activities via Zoom through material presentations and interactive discussions The results of these activities are that the employee is able to understand and improve their ability to make financial statements according to accounting standards, know their tax equalization, and understand solutions to avoid tax disputes. This activity has direct benefits for increasing participants' knowledge of procedures for recording operational transactions and a thorough understanding of tax rulesnand expected to avoid tax dispute problems